Improvement of recovered activity and stability of the Aspergillus oryzae β-galactosidase immobilized on duolite A568 by combination of immobilization methods - Falleiros Larissa Nayhara Soares Santana (Chemical Industry and Chemical Engineering Quarterly, 2017)
The immobilization and stabilization of Aspergillus oryzae β-galactosidase on DuoliteA568 was achieved using a combination of physical adsorption, incubation step in buffer at pH 9.0 and cross-linking with glutaraldehyde and in this sequence promoted a 44% increase in enzymatic activity as compared with the biocatalyst obtained after a two-step immobilization process (adsorption and cross-linking). The stability of the biocatalyst obtained by three-step immobilization process (adsorption, incubation in buffer at pH 9.0 and cross-linking) was higher than that obtained by two-steps (adsorption and cross-linking) and for free enzyme in relation to pH, storage and reusability. The immobilized biocatalyst was characterized with respect to thermal stability in the range 55-65 °C. The kinetics of thermal deactivation was well described by the first-order model, which resulted in the immobilized biocatalyst activation energy of thermal deactivation of 71.03 kcal/mol and 5.48 h half-life at 55.0 °C.